O Plano Diretor de Chapecó (SC) e a possibilidade de um pacto social à luz dos princípios do Estatuto da Cidade - Monica Hass; Myriam Aldana; Rosana Maria Badalotti (Ciências Sociais Unisinos)
With the obligation to work out a Master Plan in cities with more than 20 thousand inhabitants, on the basis of instruments and participative principles defined by the City Statute, there is a need to establish a social pact between government, market and civil society on urban policy. In view of the different interests of the actors involved in the discussion, the article analyzes the conflicts that surfaced in the debate about the reformulation (2002/2003) and revision (2006) of the Master Plan of Territorial Development of Chapecó, in the light of the principles of the City Statute and the possibility of a minimal and lasting consensus among the participants. It points out the limits of the legal instruments that try to reduce inequalities, segregations and social exclusions in view of the strength of the interests of property and land speculation.